2007
DOI: 10.1111/j.1365-2222.2007.02752.x
|View full text |Cite
|
Sign up to set email alerts
|

The changing face of food hypersensitivity in an Asian community

Abstract: In contrast to previously reported low peanut allergy rates in Asia, in our review, peanut sensitization is present in 27% (62/227) of food-allergic children, mostly in patients with multiple food protein sensitizations. Temporal patterns of first exposure of infants to fish and shellfish are unique to the Asian diet. Shellfish are a major sensitizing food source in Asian children, especially in allergic rhinitis patients sensitized to cockroaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
69
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(78 citation statements)
references
References 31 publications
(39 reference statements)
8
69
0
1
Order By: Relevance
“…It is possible that despite rapid urbanisation in Singapore, maintenance of traditional dietary practices such as early introduction of egg and fish in rice porridge, and peanut in soups may have contributed to the low rates of food allergy. (46) This would be in keeping with current knowledge and theories that early consumption of peanut and egg may prevent food allergy. (24) Another interesting practice observed in Singapore is that many community doctors still advise that egg be introduced by one year of age, or even reintroduced if there is a history of mild egg allergy before the uptake of the measles, mumps and rubella (MMR) vaccine.…”
Section: Pr E V Entio N O F Foo D a Llergymentioning
confidence: 52%
See 1 more Smart Citation
“…It is possible that despite rapid urbanisation in Singapore, maintenance of traditional dietary practices such as early introduction of egg and fish in rice porridge, and peanut in soups may have contributed to the low rates of food allergy. (46) This would be in keeping with current knowledge and theories that early consumption of peanut and egg may prevent food allergy. (24) Another interesting practice observed in Singapore is that many community doctors still advise that egg be introduced by one year of age, or even reintroduced if there is a history of mild egg allergy before the uptake of the measles, mumps and rubella (MMR) vaccine.…”
Section: Pr E V Entio N O F Foo D a Llergymentioning
confidence: 52%
“…The shift in peanut sensitisation patterns in atopic children from fourth to second place was the initial signal of this change. (25)(26)(27) In a recent study by Liew et al, peanut was found to be the top cause of anaphylaxis in a Singapore paediatric emergency centre, (28) whereas it was an absent cause of food anaphylaxis 14 years ago. (29) It is therefore important for medical professionals to watch for this rise in peanut allergy, as it is a frequent cause of fatal anaphylaxis, particularly in adolescents, and is carried into adulthood, with less than 10% outgrowing this allergy.…”
Section: Peanutmentioning
confidence: 99%
“…Survey results from Spain show that the majority of adults in general population are sensitive to one or two foods (86.7%) (14). Majority of people were sensitive to one food in Portugal (67.6%) and Singapore (70%) (15,16). Research in Northern Europe shows that the majority (95%) of patients from Sweden, Denmark, Estonia, Lithuania and Russia, that already have food hypersensitivity, are allergic to more than one food (17).…”
Section: Discussionmentioning
confidence: 99%
“…In all these countries children experienced adverse reactions from food more often than adults (17,23). In France the most common allergens were rosehips (14%), vegetables (9%), milk (8%), and crustaceans (8%), also eggs (4%) and nuts (3%) (24); in Portugal they were fresh fruits (25%) (15); in Spain such allergens were fruits (56.6%) and nuts (22.6%) (25); in United Arab Emirates the most common allergens were eggs, fruits, and fish (26); in Singapore they were eggs (40%), crustaceans (39.0%), peanuts (27.3%), and milk (11.4%) (16). R. J. Rona's meta-analysis data reveal that according to various studies, hypersensitivity to milk varies from 1.2 to 17%, to egg from 0.2 to 7%, to peanut and fish up to 2%, to crustaceans up to 10% (7).…”
Section: Discussionmentioning
confidence: 99%
“…En los países asiáticos, donde el consumo es bastante alto, la prevalencia es mayor (14). En los Estados Unidos, según una encuesta telefónica, se estimó que la prevalencia de alergia a los mariscos era del 38 %, y era más frecuente en adultos que en niños y en hombres que en mujeres (15).…”
Section: Alergia Al Camarón Una De Las Alergias Alimentarias Más Freunclassified